Safeguarding Indigenous Papuan Candidacy: Legal Certainty in the Papuan People’s Assembly Verification Process - Heru Andryana Suherman; Retno Saraswati; Lita Tyesta Addy Listya Wardhani; Hera Fauziah Lubis; Robithul Islam (RechtIdee, 2026)
Study Objective: This study examines the role and authority of the Papuan People's Assembly (MRP) in the selection mechanism for Indigenous Papuan (OAP) regional head candidates following Constitutional Court Decision Number 41/PUU-XXII/2024. The main focus of this study is on how strengthening the regulations and legal position of the MRP can ensure legal certainty and prevent political manipulation by local elites and external actors.Method/Approach: The approach used in this study is normative juridical, examining Papua's special autonomy regulations, Constitutional Court decisions, and other relevant documents and literature.Novelty: Focus on the Maqasid Syariah perspective and on strengthening regulation to maintain substantive justice and protect the rights of indigenous Papuans, across the dimensions of religion (ḥifẓ ad-dīn), soul (ḥifẓ an-nafs), reason (ḥifẓ al-‘aql), descendants (ḥifẓ an-nasl), and property (ḥifẓ al-māl).Findings: In addition to its representative and cultural functions, the MRP also has a strategic function in political education and in maintaining inclusive leadership, aligning with the values of local wisdom and remaining free from interests that distort the meaning of autonomy.Conclusion: It is important to require regulatory revision to strengthen the legitimacy and effectiveness of the MRP's role going forward.